Shabbat : recipes and rituals from my table to yours - Sussman, Adeena (Avery, an imprint of Penguin Random House, 2023)
"The author of Sababa returns with a collection of good-for-the-soul recipes that embody the spirit and pleasures of Shabbat. As a child, Adeena Sussman looked forward to the magic of Shabbat--the traditional Jewish day of rest--all week. A treasured time when family and friends come together to relax, unwind, and revel in one another's company during an open-ended, tantalizing meal, Shabbat has been practiced all over the world, and throughout history. In Adeena's home, then and now, the Shabbat table is a centering force, a nourishing place where one and all are welcome. It's an opportunity every week to feed the soul. Because tradition dictates that the Sabbath is reserved for downtime, Shabbat cooking is all about smart cooking techniques and sound prep. Nostalgic, cozy mains like Fig & Pomegranate Brisket and Bubbe's Extra-Crispy Potato Kugel are crowd-pleasers and require little hands-on attention. Sides and bright salads like Moroccan Carrot Salad, Roasted Kohlrabi, Cherry Tomato & Feta Salad, and Sweet & Tart Eggplant Salad are best served at room temperature. With staples like Amba (pickled mango spread), Tomato Jam, and Schug-a-churri (a blend of Yemenite and South American condiments) on hand, it's easy to punch up flavor and find something delectable to slather on challah. And from the showstopping Lemon Black-Sesame Bundt Cake to the rich comfort of Vegan Rice Pudding, there's always something special for dessert."--